JENIS LICHENES DI KAWASAN GUGOP PULO BREUH KECAMATAN PULO ACEH KABUPATEN ACEH BESAR - Mulyadi Mulyadi (Biotik, 2017)
The purpose of this research is to know the type of Lichens in the Gugop Pulo Breuh area, Pulo Aceh District, Aceh Besar. The subjects of this study are all types of Lichens found in the Gugop Pulo Breuh area, Pulo Aceh District, Aceh Besar. This research uses Random sampling technique with combination of line transect and quadratic method. Line transect measuring 100 m x 20 m as many as 3 stations with details of length 100 m and width 20 m. Square plot is determined systematically on each station with a size of 10 m x 10 m, as much as 3 plots to obtain 9 plot of squares. The results of the study found 2300 individu lichens samples covering 10 family of 15 species. Lichens found in the study sites consisted of two types of morphology of the talus namely Crustose and Foliose.